Evaluating Pharmaceutical Compounding Practices and Quality Management Gaps in Nigeria - Alfa, John; Amlogu, Abraham; Abdulganiyu, Qazeem; Lawal, Ibrahim (British Journal of Healthcare and Medical Research, 2026)
In Nigeria, compounding practices have historically been confined mainly to hospital and institutional pharmacies and remain relatively under-documented despite their clinical significance. This study assessed the current practices, challenges, and future directions of pharmaceutical compounding in Nigeria, with the aim of identifying gaps in training, regulation, infrastructure and quality assurance that influence the safety and effectiveness of compounded medications. A descriptive cross-sectional mixed-methods design was employed. The quantitative component involved a structured questionnaire administered to registered pharmacists engaged in compounding activities, while the qualitative component consisted of Key Informant Interviews (KIIs) with experienced pharmacists from hospital, institutional, and regulatory settings. Quantitative data were analyzed using descriptive and inferential statistics in SPSS, while qualitative data were examined through thematic analysis to identify recurring professional and institutional themes. Integration of both datasets enabled triangulation and a comprehensive interpretation of findings. A total of 69 valid survey responses were analyzed. Results indicated that most pharmacists possessed at least a Bachelor of Pharmacy or Pharm. D qualification and reported moderate to high familiarity with compounding practices. However, only about one-third had received formal or specialized compounding training beyond undergraduate education. Non-sterile compounding—such as oral suspensions, creams, and capsules—was the predominant practice, with sterile compounding performed by fewer than 10% of respondents due to inadequate facilities. Key challenges identified included limited access to quality raw materials, insufficient infrastructure, regulatory ambiguity, and the absence of standardized operating procedures and validated stability data. Qualitative findings further highlighted reliance on informal learning, gaps in regulatory enforcement, and concerns regarding quality assurance and patient safety. Overall, the study demonstrates that while pharmaceutical compounding remains an essential component of healthcare delivery in Nigeria, systemic limitations hinder its optimal practice. Strengthening regulatory frameworks, expanding professional training, improving infrastructure, and developing national compounding guidelines are essential to enhance quality, safety, and sustainability in pharmaceutical compounding practice